Tuberculosis of the knee joint: a case report - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2008)
Tuberculosis may develop in the skeletal system apart from its primary location, the lungs. A 22-year-old male patient presented with complaints of severe pain and swelling in the left knee and difficulty in walking. The symptoms first appeared 12 years before and he underwent open surgical debridement and arthroscopic debridement at two other centers, at which time aspiration cultures taken from the knee yielded no growth. Physical examination showed a painful left knee with swelling, increased temperature, effusion, and limited range of motion. Based on history, physical examination, radiological studies, and laboratory findings, knee osteoarthritis was considered secondary to nonspecific septic arthritis and knee arthrodesis was performed. At surgery, marked destruction of articular cartilage and synovial hypertrophy were observed. In addition, a cavitary lesion was detected, about 1x1 cm in size, in the lateral femoral condyle without articular involvement. Biopsy cultures taken from the lesion showed growth of Mycobacterium tuberculosis in the third week. This enabled a diagnosis of tuberculosis of the knee joint and antituberculous drug therapy was instituted. At six months postoperatively, the patient was on antituberculous treatment and had a painless knee.
Keywords: antitubercular agents; arthritis; diagnosis, differential; knee joint; tuberculosis, osteoarticular/radiography/surgery; OSTEOARTICULAR TUBERCULOSIS